PENGARUH INVESTASI DAN AGLOMERASI TERHADAP PERTUMBUHAN EKONOMI KABUPATEN/KOTA KALIMANTAN BARAT 2009-2013 - B01111043, Haekal Hamzar (Jurnal Pembangunan dan Pemerataan, 2017)
Hamzarhaekal@gmail.comABSTRACTThis study entitled "Effect of Agglomeration Of Investment And EconomicGrowth Regency / City of West Kalimantan 2009-2013". The purpose of this study wasto examine and analyze the Influence of Agglomeration Of Investment And EconomicGrowth Regency / City of West Kalimantan 2009-2013. This type of research isdescriptive quantitative research, with the aim to portray and explain the influence ofindependent variables (investment) and (agglomeration) on the dependent variable(economic growth) in West Kalimantan. This study used multiple linear regressionanalysis tool.To see the panel data regression there are some tests that need to be done inselecting the right model, the significance test fixed effect or Chow test F-test andHausman test. So do chow test results can be seen that the prob is less than 5%, it can beconcluded that the fixed effect model is more appropriate to use than on a modelcommon effect. So it is necessary to test Husman test. that the test results Husman testthe 0.0015 probability value less than 0.05% can be concluded Husman models moreprecise test used is the fixed effect of the random effect, or in other words Ho rejectedand Ha accepted.The result showed that investment and significant positive effect on economicgrowth, it is proved by testing the t-statistic coefficient value of 0.931838 and 0.0000probability value of less than or less than 0.05%. Agglomeration and no significantnegative effect on economic growth, it is proved by testing the t-statistic coefficientvalue of -0.001524 and probability value of 0.9791 greater or less than 0.05%.Keywords: Investment, Agglomeration, and Economic Growth.